2015
DOI: 10.1007/s00394-015-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionately increased 24-h energy expenditure and fat oxidation in young men with low birth weight during a high-fat overfeeding challenge

Abstract: We suggest that disproportionally enhanced fat oxidation in LBW individuals during short-term HFO represents a compensatory response to reduced subcutaneous adipose tissue expandability and storage capacity. The extent to which this mechanism may lead to, or be replaced by insulin resistance, ectopic fat accumulation and/or glucose intolerance during long-term HFO in LBW needs further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
(52 reference statements)
4
14
0
Order By: Relevance
“…Low birth weight and NBW men displayed differences in body composition and glucose and lipid metabolism after the control and high‐fat, high‐calorie diets, and both birth weight groups showed changes in metabolism in response to the dietary challenge, as previously reported (Brons et al. , , , ). A selection of variables that provide background for the current findings is shown in Tables and and also presented here.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Low birth weight and NBW men displayed differences in body composition and glucose and lipid metabolism after the control and high‐fat, high‐calorie diets, and both birth weight groups showed changes in metabolism in response to the dietary challenge, as previously reported (Brons et al. , , , ). A selection of variables that provide background for the current findings is shown in Tables and and also presented here.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, calorimetry was performed throughout 24 h from the first to second study day by use of a respiratory chamber and in the basal and insulin‐stimulated steady‐state periods of the clamp to evaluate substrate utilization rates and energy expenditures, as previously described (Brons et al. , , ). Blood samples were collected prior to and during the clamp.…”
Section: Methodsmentioning
confidence: 99%
“…In strong support of the 'thrifty phenotype' hypothesis as proposed by Hales and Baker (10), we have previously shown that young SGA men exhibit decreased energy expenditure when subjected to 36-h fasting (11). Furthermore, recent data suggest that young healthy SGA men may have an altered diurnal rhythm including diurnal variations in metabolic hormones compared with control individuals born appropriate for gestational age (AGA), since they exhibit pronounced differences in substrate oxidation rates in particular during nighttime (12,13). A central clock located in the suprachiasmatic nucleus (SCN) in the hypothalamus, generating a circadian (24-h) rhythm, regulates most physiological functions.…”
Section: Introductionsupporting
confidence: 55%
“…This hypothesis was based on the studies of 24-h substrate oxidation rates in SGA and AGA controls, the finding of increased nocturnal fat oxidation in SGA men (12,13), as well as on our previously reported increased rate of lipolysis as determined using a stable isotope glycerol tracer in the fasting state among young men born SGA (7). However, in this study, no difference in plasma FFA levels between the groups was documented during nighttime.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation